Pentingnya Kesemaptaan Jasmani bagi Tenaga Pendidik terhadap Kinerja Mengajar di Sekolah - Sari, Novita; Sembiring, Zamalluddin (YASIN, 2025)
Physical fitness is an important factor that can influence the quality of teachers' classroom performance. This study aims to analyze the effect of physical fitness on teaching performance among teachers in Serdang Bedagai Regency. A quantitative method and literature review were employed using a descriptive approach. The research population consisted of all educators in the area, with a sample of 15 individuals selected randomly. Data collection techniques included questionnaires, observation, and documentation, while data analysis was carried out using descriptive quantitative methods. The results indicate a positive and significant relationship between physical fitness and teaching performance. Teachers with good physical fitness levels demonstrated higher attendance and punctuality, more comfortable interaction with students, more effective delivery of learning materials, and better classroom management. The conclusion of this study is that physical fitness should be a focus in efforts to improve teacher performance in the classroom. The practical implications of these findings suggest the need for light physical activities, such as ice breaking or light exercises, before starting the teaching process to support teachers' physical condition and teaching enthusiasm.